Manajemen Pendidikan Karakter di Sekolah Indonesia Kota Kinabalu, Sabah-Malaysia - Purwanto, Edi; Karwanto, Karwanto; Khamidi, Amrozi; Nursalim, Mochamad (LP. Ma'arif Janggan Magetan, 2024)
This study aims to determine the management of Character Education in Indonesian Schools in Kota Kinabalu, Sabah - Malaysia which includes the planning, implementation and evaluation processes. This study is a qualitative study using a descriptive approach, the results of this study are not to find relationships or influences but rather to describe or map the phenomenon clearly. The selection of research subjects was carried out using the purposive sampling technique. Data collection through interviews, observations, and documentation. Data validity using triangulation techniques. Data analysis using data reduction, data presentation, and drawing conclusions. The results of the study indicate that the management of Character Education in Indonesian Schools in Kota Kinabalu, Sabah - Malaysia is carried out through three stages, namely; the planning stage, the school holds a meeting involving the entire school community to formulate what character values will be developed, the program and how the implementation mechanism is. At the implementation stage, instilling Character Education in students is carried out through integration with the school curriculum, extracurricular activities, school culture, school regulations and cooperation with stakeholders. Furthermore, the school conducts periodic evaluations to see the results of the Character Education instillation program for students running optimally according to school goals or not. The management of character education at Sekolah Indonesia Kota Kinabalu, Sabah-Malaysia, has shown success in shaping students' characters through a planned, holistic approach, and involving various parties. With continuous strengthening of management, this school can continue to be a model in the implementation of cross-cultural character education in border areas. In addition, the success of Sekolah Indonesia Kota Kinabalu in shaping positive characters in students has also motivated the Community Learning Center (CLC) to implement the same thing in their respective CLCs.